2008
DOI: 10.1515/epoly.2008.8.1.1800
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of galbanic acid on photo-oxidative degradation of linear low density polyethylene (LLDPE) films

Abstract: Photo-oxidative degradation of LLDPE films (~ 250 μm thick) containing varying amounts of galbanic acid (a type of coumarin derivatives) was investigated by exposing the films to an artificial sunlight (emitted by 300 W OSRAM UltraVitalux lamps) at 40 ○ C for extended time periods. Photo-oxidative degradation of the neat polymer film and the LLDPE films containing benzophenone (an active photo-initiator for PE) and coumarin alone were also studied under similar conditions for comparison. The rate of photo-oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…According to (Wang et al 2018), the most abundant microplastic forms in Hong Lake and Dongting Lake were polyethylene and polypropylene. Gopinath et al (2020) identi ed high-density polyethylene and polypropylene microplastics in Chennai's Red Hills Lake, and their spectra show similar characteristic peaks 2919 and 2847 cm − 1 (-CH), 1470 cm − 1 (-CH), and 716 cm − 1 (-CH) of polyethylene and polypropylene spectra shows wavenumbers of 2866 cm − 1 , 2836 cm − 1 , 2950 cm − 1 as well as linear low-density polyethylene microplastic were also reported in (Jahanmardi and Assempour 2008) studies. These polymer types are widespread in lakes and may oat and move long distances in wind and water due to their low density (High-density polyethylene:0.93 to 0.97 g/cm 3 , Linear low-density polyethylene: 0.915-0.925 g/cm 3 , and Polypropylene:0.85 g/cm 3 ) (Ashraf 2015).…”
Section: ) Jian Et Al (2020) Also Reported That the High Abundance Of...supporting
confidence: 55%
“…According to (Wang et al 2018), the most abundant microplastic forms in Hong Lake and Dongting Lake were polyethylene and polypropylene. Gopinath et al (2020) identi ed high-density polyethylene and polypropylene microplastics in Chennai's Red Hills Lake, and their spectra show similar characteristic peaks 2919 and 2847 cm − 1 (-CH), 1470 cm − 1 (-CH), and 716 cm − 1 (-CH) of polyethylene and polypropylene spectra shows wavenumbers of 2866 cm − 1 , 2836 cm − 1 , 2950 cm − 1 as well as linear low-density polyethylene microplastic were also reported in (Jahanmardi and Assempour 2008) studies. These polymer types are widespread in lakes and may oat and move long distances in wind and water due to their low density (High-density polyethylene:0.93 to 0.97 g/cm 3 , Linear low-density polyethylene: 0.915-0.925 g/cm 3 , and Polypropylene:0.85 g/cm 3 ) (Ashraf 2015).…”
Section: ) Jian Et Al (2020) Also Reported That the High Abundance Of...supporting
confidence: 55%
“…Investigations of photo-oxidative degradation of LLDPE films containing various amounts of GA revealed that GA was highly effective in accelerating photooxidation of LLDPE films. Jahanmardi and Assempour (2008a) reported that an outstanding acceleration of photooxidation observed for the film containing 0.2% wt of GA in comparison with the film containing the same amount of benzophenone. Also, GA was known as an effective photosensitizing agent in polyethylene.…”
Section: Total Synthesis Of Gamentioning
confidence: 99%